Environmental Profile of Two Soil Remediation Options – A Case Study in Northern Alberta - Amponsah, Nana Y.; Wang, Junye; Zhao, Lian (Journal of Environmental Accounting and Management, 2026)
Contaminated soil and groundwater are environmental hazards that pose a serious threat to human health. Across Alberta, Albertans are increasingly demanding cleanup of contaminated sites located in or close to their communities. Hydrocarbon spills that often occur during oil and gas operations result in loss of soil quality and contamination of groundwater. This may reduce transport of water and air, inhibit microbial activity, and nutrient cycling. The objective of this paper is to introduce life cycle assessment (LCA) within the existing framework of phased environmental site assessments (ESAs) in the selection of soil remedial alternatives for oil and gas well site clean ups. The ESA-LCA analysis involves processing inputs from the ESA findings to the LCA software (SIMAPRO), identifying the remedial alternatives to compare, running the LCA model using these inputs; and conducting an uncertainty analysis via Monte Carlo Simulation (MCS). A case study comparing two common soil remediation alternatives was presented to demonstrate the improved framework at a well site in Northern Alberta. The LCA results show favorable environmental impact indicators for bioventing over excavation and biopile treatment. This shows the LCA methodology as an excellent tool to compare different remediation options and can be used as a decision- making tool for authorities. An increased focus is recommended in policy discussions on understanding the long term environmental impacts of oil and gas well site remediation options.